Topnaar or Hottentot? The People on the Top Revisited - Van Damme, Patrick; Van Den Eynden, Veerle (Afrika Focus, 1992)
The Topnaar which live in the Namib Desert have only been studied superficially. This article gives some sociological, historical and general interest information about these wonderful people